RELIGIOUS HUMANISM IN ISLAMIC EDUCATION - Irhas Sya'bana (EZRA SCIENCE BULLETIN, 2023)
The model for creating a religious atmosphere is strongly influenced by certain situations and conditions and the application of the underlying values, namely: the structural model, the formal model, the mechanical model, and the organic model. First, the structural model, namely the creation of a religious atmosphere that is encouraged by the existence of regulations, impression building, and policies of an institution or organization and is more of a top-down nature. Second, the formal model, namely the creation of a religious atmosphere based on the understanding that religious education is a human effort to work only on the problems of the afterlife / spiritual life. Third, the mechanical model is the creation of a religious atmosphere based on the understanding that education is seen as the inculcation and development of a set of life values that work according to their function, which emphasizes moral and spiritual functions or the affective dimension rather than cognitive and psychomotor. Fourth, the organic model, namely the creation of a religious atmosphere that is encouraged by the view that religious education is a unit that develops religious views and enthusiasm for life which is manifested in religious attitudes and life skills.